The influence of the secondary building linker geometry on the photochromism of naphthalenediimide-based metal–organic frameworks. Issue 33 (1st August 2018) - Fu, Chen; Wang, Hai-Yu; Zhang, Guo-Shuai; Li, Li; Sun, Ya-Nan; Fu, Jia-Wei; Zhang, Hong
Abstract : The photochromism of three MOFs based on NDI chromophores is mainly induced by two kinds of non-covalent intermolecular interactions. Abstract : Three novel square grid metal–organic frameworks (MOFs) based on cadmium have been synthesized successfully by analogous solvothermal reactions where N, N ′-di(4-pyridylacylamino)-1, 4, 5, 8-naphthalenediimide (IsoNDI) as the predesigned ligand was reacted with three kinds of aromatic dicarboxylic acids as the secondary building linkers. The geometries of these secondary building linkers have an influence on the formation of photochromism-leading intermolecular interactions in the obtained crystal structures. Owing to the existence of an NH group in the adopted NDI-type ligand, N–H⋯O hydrogen bonds are observed between the IsoNDI ligands and neighbouring dicarboxyl groups in all the compounds. However, face-to-face π–π stacking interactions are only found in compound1 and not in2 and3, for the naphthalene ring possessing a larger π-plane in1 is more likely to form interactions with the π-conjugated planar IsoNDI ligand. Meanwhile, lone pair–π interactions appear in compounds2 and3 but not in1 because their close packing patterns have a tendency to generate such interactions between adjacent IsoNDI ligands. Moreover, all three compounds exhibit interesting reversible photochromic behaviors in the presence of photoinduced electron transfers through the above intermolecular interactions. Besides, photo-controlled luminescence properties have also been investigated showing a competitive relationship with photochromic behaviors.